Parotid Collector - Dietrich, T. A. (1964)
This instrument was developed for NASA by Beckman Instruments' Space Engineering Group (SEG) in 1964. The SEG developed this prototype hardware to store and analyze saliva from astronauts as part of monitoring their medical condition.
Keywords: Parotid glands--Innervation; Scientific apparatus and instruments; Saliva; Beckman Instruments, Inc.